Clinical impact of rest dual-energy computed tomography myocardial perfusion in patients with coronary artery disease - Baumann, Stefan; Becher, Tobias; Haubenreisser, Holger; Vogler, Nils; Borggrefe, Martin; Schönberg, Stefan; Akın, Ibrahim; Henzler, Thomas; Loßnitzer, Dirk (In vivo, 2017)
Background/Aim: To evaluate the hypothesis that patients with suspected coronary artery disease (CAD) assessed using rest dual-energy computed tomography-derived myocardial perfusion imaging (DECT-P), could have fewer invasive coronary angiographies (ICA), showing non-obstructive CAD. Materials and Methods: Patients who had undergone coronary computed tomography angiography (cCTA), rest DECT-P and ICA were analyzed. Results: We evaluated 51 patients (62.7% males, mean age 51.6±12.8 years). Rest DECT-P identified perfusion defects in three (10.7%) of the 28 patients with cCTA negative for luminal stenosis and in 10 (43.5%) of the 23 patients with cCTA positive for luminal stenosis. In total, 21 patients underwent both cCTA and ICA, of which seven (33.3%) showed obstructive CAD. Rest DECT-P revealed false-negative results in four cases (19.1%) and false-positive results in six cases (28.6%). Conclusion: Adding rest DECT-P to cCTA has no incremental diagnostic value over cCTA alone, to exclude haemodynamically significant CAD. Therefore, a rest-stress-DECT-P protocol or a CT-based FFR calculation might be a promising concept to improve diagnostic accuracy in a real clinical setting.
Gesehen am 04.04.2018